2016
DOI: 10.1186/s13195-016-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Grey matter atrophy in prodromal stage of dementia with Lewy bodies and Alzheimer’s disease

Abstract: BackgroundLittle is known about the patterns of brain atrophy in prodromal dementia with Lewy bodies (pro-DLB).MethodsIn this study, we used SPM8 with diffeomorphic anatomical registration through exponentiated lie algebra to measure grey matter (GM) volume and investigate patterns of GM atrophy in pro-DLB (n = 28) and prodromal Alzheimer’s disease (pro-AD) (n = 27) and compared and contrasted them with those in elderly control subjects (n = 33) (P ≤ 0.05 corrected for family-wise error).ResultsPatients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 54 publications
(69 reference statements)
2
74
2
2
Order By: Relevance
“…However, we applied a highly structured, systematized approach to thoroughly detect the core features of DLB including fluctuating cognition (Walker et al, ) and visual hallucination (Cummings et al, ), and clinically suspected DLB cases performed additional PET studies such as an 18 F‐fludeoxyglucose PET scans to check whether they demonstrated supportive imaging biomarkers for DLB (McKeith et al, ). This effort may minimize the misclassification of prodromal DLB cases (Blanc et al, ) into the PD‐MCI cases. Finally, compared to our previous study (Lee et al, ), the current study has several strengths, including a more sophisticated study design, criteria for classifying PDD converters that are more stringent, a larger sample size, and longer follow‐up duration, as well as methodological improvements in the neuroimaging analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, we applied a highly structured, systematized approach to thoroughly detect the core features of DLB including fluctuating cognition (Walker et al, ) and visual hallucination (Cummings et al, ), and clinically suspected DLB cases performed additional PET studies such as an 18 F‐fludeoxyglucose PET scans to check whether they demonstrated supportive imaging biomarkers for DLB (McKeith et al, ). This effort may minimize the misclassification of prodromal DLB cases (Blanc et al, ) into the PD‐MCI cases. Finally, compared to our previous study (Lee et al, ), the current study has several strengths, including a more sophisticated study design, criteria for classifying PDD converters that are more stringent, a larger sample size, and longer follow‐up duration, as well as methodological improvements in the neuroimaging analyses.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the increased RT in the LBD group is a result of delayed onset of task related cognitive activity, and hence slower processing. These regions are all affected in LBD, with metabolic reductions in the occipital and parietal lobes (Firbank et al, ; Kantarci et al, ), reports of reduced grey matter in the insula (Blanc et al, ; Xu et al, ) and cholinergic (Mazère et al, ) and dopaminergic (O'Brien et al, ) alterations in the BG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a reduction in dopaminergic receptor binding and grey matter density have been associated with mild cognitive impairment in PD . Insular atrophy was also found in patients with prodromal DLB and correlates with impairment in attributing mental states to others in patients with probable DLB .…”
Section: Introductionmentioning
confidence: 98%